faktor-faktor yang berhubungan dengan kinerja kader dalam pemberdayaan masyarakat di Posyandu Berbasis Integrasi Layanan Primer (ILP) Puskesmas Margahayu Raya Kota Bandung - RIYANTO, AGUS; Irianto, Gunawan; Laili, Ayu; Dian Abdillah, Asep; Safitri, Aulia (JURNAL KESEHATAN KARTIKA, 2025)
Background: Posyandu cadre performance plays an important role in supporting the successful implementation of the Primary Service Integration (ILP) program, especially in community empowerment efforts in the health sector. Based on data in the working area of Margahayu Raya Health Center, Bandung City, the achievement of mosquito larvae-free houses shows fluctuations that have not consistently reached the target of above 95% every month. This indicates challenges in achieving optimal cadre performance. Cadre performance can be caused by several factors including education, length of service, knowledge, attitude, motivation, workload and training. Objective: The purpose of this study was to determine factors related to cadre performance in Community Empowerment at Integrated Primary Service Posts (ILP) of Margahayu Raya Health Center, Bandung City. Method: This study uses a quantitative approach using a Cross Sectional design. The sample in this study was 110 people. Data analysis using the chi square test. Results: The results showed that most cadres had good performance (58.2%). There was a significant relationship between length of service (p = 0.015), knowledge (p = 0.036), attitude (p = 0.0001), motivation (p = 0.0001), and workload (p = 0.001) with cadre performance. Meanwhile, the variables of education (p = 0.069) and training (p = 0.547) did not show a significant relationship. Conclusion: There is a significant relationship between length of service, knowledge, attitude, motivation, and workload with cadre performance. In relation to this study, the author suggests that health centers conduct ongoing coaching, increase motivation, and strengthen the capacity of cadres to support the effectiveness of the implementation of Integrated Primary Service-based Posyandu.